2014
DOI: 10.4172/2169-0049.1000115
|View full text |Cite
|
Sign up to set email alerts
|

Watershed Prioritization using Morphometric and Land Use/Land Cover Parameters of Dudhganga Catchment Kashmir Valley India using Spatial Technology

Abstract: Watershed prioritization has gained importance in natural resources management, especially in the context of watershed management. Morphometric and land use analysis has been commonly applied to prioritization of watersheds. In the present study, prioritization on the basis of morphometricand land use analysis of watersheds have been performed for the Dudhganga catchment of Kashmir Valley J&K. Various morphometric parameters, namely linear and shape have been determined for each watersheds and assigned ranks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The bifurcation ratio is defined as the ratio between the total number of tributaries in a particular order and the total number of the tributaries in the next order [63,66]. The bifurcation rate indicates the shape of the basin and the response to erosion, in addition to the geological structure of the area.…”
Section: Bifurcation Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…The bifurcation ratio is defined as the ratio between the total number of tributaries in a particular order and the total number of the tributaries in the next order [63,66]. The bifurcation rate indicates the shape of the basin and the response to erosion, in addition to the geological structure of the area.…”
Section: Bifurcation Ratiomentioning
confidence: 99%
“…The gradient ratio is defined as the ratio between the difference of the depths in the drainage basin and the length of the drainage basin [66]. The gradient ratio affects all geomorphometric characteristics of the water drainage properties, including the amount of surface runoff, intrusion rates, drainage intensity, flood severity, and erosion rates.…”
Section: Gradient Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Landform processes and erosional characteristics that are statistically represented constitute morphometry and are substantial in describing the peculiarity of sub-watersheds through morphometric parameters. [16] Even with the connection of morphometry and land use-land cover (LU/LC), [17] tries to give some better characterization of watershed by superimposing of the morphometric parameters and LU/LC layers.…”
Section: Change Detectionmentioning
confidence: 99%
“…They found that 51.66% of sub-watersheds were in the moderately to highly susceptible zones. Iqbal & Sajjad (2014) prioritized five watersheds, D1A, D1B, D1C, D2A, D2B of Dudhganga catchment. It was found that D1C and D1A fall under high and medium priority respectively.…”
Section: Introductionmentioning
confidence: 99%